Efficacy and Safety of Atacicept in Patients With Systemic Lupus Erythematosus: Results of a Twenty‐Four–Week, Multicenter, Randomized, Double‐Blind, Placebo‐Controlled, Parallel‐Arm, Phase IIb Study. Issue 2 (29th January 2018) - Merrill, Joan T.; Wallace, Daniel J.; Wax, Stephen; Kao, Amy; Fraser, Patricia A.; Chang, Peter; Isenberg, David; ,
Abstract : Objective: To evaluate the efficacy and safety of atacicept, an antagonist of B lymphocyte stimulator/APRIL–mediated B cell activation, in patients with systemic lupus erythematosus (SLE). Methods: ADDRESS II is a 24‐week, multicenter, randomized, double‐blind, placebo‐controlled, parallel‐arm, phase IIb study evaluating the safety and efficacy of atacicept in patients with SLE (ClinicalTrials.gov identifier NCT01972568). Patients with active, autoantibody‐positive SLE receiving standard therapy were randomized (1:1:1) to receive atacicept (75 mg or 150 mg) or placebo for 24 weeks. The primary end point was the SLE responder index 4 (SRI‐4) at week 24. Results: The intent‐to‐treat (ITT) population included 306 patients. There was a trend toward an improved SRI‐4 response rate with atacicept 75 mg (57.8%; adjusted odds ratio [OR] 1.78, P = 0.045) and 150 mg (53.8%; adjusted OR 1.56, P = 0.121) at week 24 as compared with placebo (44.0%) (primary analysis; using the screening visit as baseline). In a prespecified sensitivity analysis using study day 1 as baseline, a significantly larger proportion of patients receiving atacicept 75 mg and 150 mg achieved an SRI‐4 response at week 24 compared with placebo. In predefined subpopulations with high levels of disease activity (HDA) at baseline, serologically active disease, or both, statistically significant improvements in the SRI‐4 and SRI‐6 response rates were seen with atacicept versus placebo. A severe risk of disease flare was reduced with atacicept therapy in both the ITT and the HDA populations. The risks of serious adverse events and serious or severe infection were not increased with atacicept as compared with placebo. Conclusion: Atacicept treatment showed evidence of efficacy in SLE, particularly in HDA and serologically active patients. Reductions in disease activity and severe flare were observed with atacicept treatment, with an acceptable safety profile.